نظام القيد في السجل التجاري - بوغرارة نسرين (المسيلة, 2023)
Registration in the commercial registry is one of the essential requirements for individuals, whether natural or legal persons, seeking to obtain commercial status. The legislator aims to cover all legal aspects of registration. The commercial registry is important in supporting credit and legal advertising, as it allows others to access the legal information of the merchant. Additionally, the commercial registry assists the state in determining the size of commercial activity and directing the economy, so it plays a statistical and informational role. After registration, the registered person obtains full commercial status and enjoys the related rights and duties. The applicant for registration must have merchant status and have activity within the national territory, and when making amendments or cancellations, they must respect all legal procedures.
Keywords: نظام القيد - السجل التجاري